Research in Interactive Design (Vol. 4) Mechanics, Design Engineering and Advanced Manufacturing - Fischer, Xavier; Daidie, Alain; Eynard, Benoit; Paredes, Manuel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Covering key topics in the field such as technological innovation, human-centered sustainable engineering and manufacturing, and manufacture at a global scale in a virtual world, this book addresses both advanced techniques and industrial applications of key research in interactive design and manufacturing. Featuring the full papers presented at the 2014 Joint Conference on Mechanical Design Engineering and Advanced Manufacturing, which took place in June 2014 in Toulouse, France, it presents recent research and industrial success stories related to implementing interactive design and manufacturing solutions.
Keywords: Engineering design; Engineering mathematics; Engineering -- Data processing; Manufactures; Engineering Design; Mathematical and Computational Engineering Applications; Machines, Tools, Processes